The Effectiveness of Quadratus Lumborum and Fascia Iliaca Blocks on Patient Outcomes in Hip Arthroplasty - Cameron Gauhl; Seaneen McDougall (Pain Research and Management)
Hip arthroplasty is a common procedure with high costs and difficult rehabilitation. It causes postoperative pain, and this can reduce mobility which extends in-patient time. An optimal analgesia regime is crucial to identify. Opioids produce effective pain relief but are associated with nausea, vomiting, and respiratory depression which can hinder physiotherapy and discharge. Finding alternatives has been of interest in recent years, particularly fascial blocks. These are anaesthetic injections beneath fascia which spread to nerves providing pain relief from surgery and are used with a general or spinal anaesthetic. Two of these blocks which are of interest to total hip arthroplasty are the quadratus lumborum block and fascia iliaca block. Studies have investigated the effectiveness of these blocks through patient factors, primarily pain scores, opioid consumption, and other secondary outcomes such as ambulation and length of stay. This review takes a narrative approach and investigates the literature around the topic. Pain and opioid consumption were the most widely reported outcomes, reported in 90% and 86% of studies. 83% of these studies reported positive effects on pain scores when FIB was utilised. 80% of these studies reported positive effects on opioid consumption when FIB was used. When QLB block was utilised, pain and opioid consumption were positively impacted in 82% of studies. This paper has been written with the intention of reviewing current literature to give an impression of the effectiveness of the blocks and propose potential areas for future work on the blocks.